2016
DOI: 10.1109/tbme.2015.2436375
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Two-Directional Two-Dimensional Principal Component Analysis and Its Application to High-Dimensional Biomedical Signal Classification

Abstract: Goal: Time-frequency analysis incorporating the wavelet transform followed by principal component analysis (WT-PCA) has been a powerful approach for the analysis of biomedical signals such as electromyography (EMG), electroencephalography (EEG), electrocardiography (ECG), and Doppler ultrasound. Time-frequency coefficients at various scales were usually transformed into a one-dimensional array using only a single or a few signal channels. The steady improvement of biomedical recording techniques has increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The final step in the EMG processing sequence is inference of movements from the reduceddimensionality feature vectors. Various classifiers have been analysed in this context, including Support Vector Machines (SVMs) [9], [10], [18], [21], [22], bayesian classifiers [14], gaussian mixture models [14], hidden markov models [14], fuzzy classifiers [14] and Multilayer Perceptrons (MLPs) [8], [16], [20], [23].…”
Section: A Wrist-hand Movement Detection Using Emgmentioning
confidence: 99%
“…The final step in the EMG processing sequence is inference of movements from the reduceddimensionality feature vectors. Various classifiers have been analysed in this context, including Support Vector Machines (SVMs) [9], [10], [18], [21], [22], bayesian classifiers [14], gaussian mixture models [14], hidden markov models [14], fuzzy classifiers [14] and Multilayer Perceptrons (MLPs) [8], [16], [20], [23].…”
Section: A Wrist-hand Movement Detection Using Emgmentioning
confidence: 99%
“…Therefore, ten time-domain features were selected for feature calculation. They were the mean absolute value (MAV) [15], root mean square (RMS) [16], Wilson amplitude (WAMP) [15], zero-crossing (ZC) [17], waveform length (WL) [18], the mean absolute value slope (MAVS) [30], slope sign change (SSC) [31], variance (VAR) [32], autoregressive (AR) coefficient of sEMG signal [27], and the AR coefficients from the first difference (FDAR) of the sEMG signal.…”
Section: Time-featuresmentioning
confidence: 99%
“…Such that the high-dimensional features can be reduced using a supervised feature reduction algorithm. Xie et al [27] have proposed a multi-scale bidirectional two-dimensional PCA method for high-dimensional biomedical signal analysis, which realized the dimensionality reduction of high-dimensional signals and proved to be highly efficient. Wang et al [28] have applied LDA classify the sEMG signals from 2 electrodes and recognize the grasping force.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus feasible to apply image processing techniques to indicate time-frequency matrix (TFM) characteristics. In a recent study, we have demonstrated the superiority of 2D 2 PCA over PCA to extract discriminant features form wavelet coefficients for high-density electrode array MES recognition (Xie et al, 2016). Despite the success of this recent 2D 2 PCA-based MES study, the involved wavelet transform exhibits some disadvantages, such as its complicated computation, sensitivity to noise level and the dependency of its accuracy on the chosen basis wavelet (Nguyen and Liao, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the performance of the proposed method, results are presented on the recognition of eight hand motions from 4-channel MESs recorded in both health subjects and amputees, aiming for the prosthetic hand, robot, and human man interface controlling. The results obtained using ST2D 2 PCA are compared with WTPCA (Huang et al, 2012), WT2D 2 PCA (Xie et al 2016), as well as the hybrid STFT and 2D2PCA (STFT2D 2 PCA) method.…”
Section: Introductionmentioning
confidence: 99%